Attention to emotional stimuli in borderline personality disorder – a review of the influence of dissociation, self-reference, and psychotherapeutic interventions. Issue 1 (December 2016) - Winter, Dorina
Abstract Interactions between attention and processing of emotional stimuli shed light on both sensitivity to emotional stimuli as well as emotion dysregulation. Both of the latter processes have been proposed as central characteristics of altered emotion processing in those with borderline personality disorder (BPD). This review first summarizes the conflicting behavioural, psychophysiological and neuroimaging evidence for the hypothesis that emotional dysregulation should be reflected by higher distractibility through emotional stimuli in those with BPD. Dissociation, self-reference, as well as symptom severity modulated by psychotherapeutic interventions are proposed to help clarify divergent findings. Data suggest an association of dissociation with impaired task continuation during the presentation of interfering emotional and neutral stimuli, as well as high recruitment of neuronal attention networks together with a blunted emotional response. Considering self-reference, evidence suggests that negative rather than positive information may be more self-relevant to those with BPD. This may be due to a negative self-concept and self-evaluation. Social or trauma-relevant information attracts more attention from individuals with BPD and thus suggests higher self-relevance. After psychotherapeutic interventions, initial evidence may indicate normalization of the way attention and emotional stimuli interact in BPD. When studying attention-emotion interactions in BPD, methodological heterogeneities regarding sample, task, and stimulus characteristics need to be considered. When doing so, dissociation, self-reference, and psychotherapeutic interventions offer promising targets for future studies on attention-emotion interactions in those with BPD. This could promote a deeper insight into the affected individuals' struggle with emotions.